2016
DOI: 10.1016/j.devcel.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Long Oskar Controls Mitochondrial Inheritance in Drosophila melanogaster

Abstract: SUMMARY Inherited mitochondrial DNA (mtDNA) mutations cause severe human disease. In most species, mitochondria are inherited maternally through mechanisms that are poorly understood. Genes that specifically control the inheritance of mitochondria in the germline are unknown. Here, we show that the long isoform of the protein Oskar regulates the maternal inheritance of mitochondria in Drosophila melanogaster. We show that during oogenesis mitochondria accumulate at the oocyte posterior concurrent with the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 59 publications
3
86
1
Order By: Relevance
“…With no identifiable orthologs in humans, CG5726 protein shows up to 50% sequence identity among Drosophilids. In early embryos of Drosophila melanogaster, CG5726 interacts with short Osk (108). In this study, we found CG5726 to be interacting with multiple RBPs: Glo, Hrp48 and Vas, suggesting its possible role in translational regulation.…”
Section: Identification Of Novel Genes With a Potential Role In Drososupporting
confidence: 51%
See 1 more Smart Citation
“…With no identifiable orthologs in humans, CG5726 protein shows up to 50% sequence identity among Drosophilids. In early embryos of Drosophila melanogaster, CG5726 interacts with short Osk (108). In this study, we found CG5726 to be interacting with multiple RBPs: Glo, Hrp48 and Vas, suggesting its possible role in translational regulation.…”
Section: Identification Of Novel Genes With a Potential Role In Drososupporting
confidence: 51%
“…Both SC35 and SF2 could be validated for their interaction with Glo and Stau, while pUF68 bound eIF4AIII and Stau in vitro. pUF68 was previously shown to interact with Hrp48 and Glo (38) and SF2 co-purifies with the short isoform of Osk (108). These results together with the well-studied role of SR proteins in cytoplasmic regulation of gene expression including mRNA export, decay and translation in mammalian systems (109,110) suggest that splicing factors are bona fide components of the mRNA localization machinery.…”
Section: Nuclear Processing Is Intrinsically Linked To Cytoplasmic Tamentioning
confidence: 65%
“…This embryonic lethality was a strict maternal effect dependent on the temperature of the mother, which rescue experiments suggest is caused by incompatibility between the nuclear Aatm V and mitochondrial tRNA tyr G:U alleles. The temperature-shift experiments suggested that early oogenesis is a temperature-sensitive period, which is known to be a crucial time for mitochondrial proliferation, transport and selection, and alleles of mitochondrial proteins can even influence early oocyte specification (Cox and Spradling, 2003;Hill et al, 2014;Hurd et al, 2016;Ma et al, 2014;Teixeira et al, 2015). Our analysis, however, did not reveal defects in mitochondrial number, transport or oocyte specification.…”
Section: Discussioncontrasting
confidence: 57%
“…In the Drosophila oocyte, streaming promotes the mixing and transport of cytoplasmic components (13,40) and is required for essential events for embryogenesis, such as the localization of mitochondria (41) and of the developmental determinant nanos mRNA (5,42).…”
Section: Discussionmentioning
confidence: 99%